EVALUATION OF SCHOOL WEBSITE BASED ON USER DEMOGRAPHICS, SATISFACTION, AND COMMUNITY RELATION - Sundari, Sri; Ali, Nor Azizah (SYNTIFIC, 2026)
Background. School website utilization is an important issue in the context of education in the digital era. Research Purpose. The purpose of this study is to analyze the school website as a digital tool for school and community relations based on the UTAUT (Unified Theory of Acceptance and Use of Technology) theory. Research Method. This type of research was a quantitative approach with a descriptive survey design. The research variables consist of UTAUT independent variables, namely performance expectancy, effort expectancy, social influence, & facilitating conditions. At the same time, the dependent variable is user demographics and satisfaction with the school website. Research January-May 2024 in several schools in Gresik by involving school employees and citizens who use the school websites of school students in Gresik. The number of respondents was 100 people, with a multiple logistic regression analysis. Findings. The UTAUT model has a significant influence on school website utilization. Performance expectancy and facilitating conditions proved to be strong predictors of school website utilization. Effort expectancy and social influence did not show a significant influence on school website utilization in this model. Demographic variables such as age and experience also showed no significant influence on school website utilization. However, gender showed a significant influence, with female respondents tending to utilize school websites more frequently than male respondents. Conclusion. Expected performance and facilitating conditions are key factors that influence school website utilization. Schools still need to consider effort and social influence aspects in their website development strategy.